Los presupuestos de gastos tributarios: Conceptos y desafíos de implementación - Luiz Villela; Andrea Lemgruber; Michael Jorratt (Inter-American Development Bank (IDB), 2009)
– Tax expenditures are generally defined as those government expenditures carried out through tax legislation, regulations, and practices that reduce or defer taxes for some taxpayers. There is a general concern that the tax expenditures negatively affect the budget and tax policies, which in turn affect the transparency, efficiency, and equality of the fiscal systems. Many countries in Latin American and a few in the Caribbean already estimate their tax expenditures; but in many cases they do so without adopting a consistent methodology that allows for adequate comparisons or that even evaluates their effectiveness. This working paper discusses the conceptual aspects of tax expenditures, the main challenges to assess them, and the general procedures adopted in the OECD countries and Latin America and the Caribbean to calculate, present, and approve them.
hdl:11319/4302
Keywords: H20; E62; 330; Tributación; Subsidios y Política Fiscal